Pengaruh Person Organization Fit Terhadap Kinerja Karyawan - Wulandari, Desi; Budiman, Fajar; Eriawati, Yossi (Institut Agama Islam Sumatera Barat Pariaman, 2023)
This research aims to find out whether Person Organization Fit has an effect on employee performance. The type of research used is quantitative research with a survey approach. The data used is primary data obtained from distributing questionnaires. There were 53 respondents who participated in this research. Data analysis and processing techniques use regression analysis, coefficient of determination (R2). From this research, the results obtained show that Person Organization Fit has an influence on employee performance. This is proven based on the results of the F test where the Fcount value > Ftable value where the Fcount value is 36.521 which is greater than Ftable 4.10, so it can be interpreted that there is an influence between Person Organization Fit on employee performance. And based on the calculation results of the coefficient of determination test (R2), it shows that the Rsquare value of the variation in the dependent variable which is influenced by the independent variable is 12%, while the remaining 88% is influenced by other factors outside this research.